2023
DOI: 10.3390/microorganisms11061568
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antifouling Strategies for Marine Applications

Abstract: Marine biofouling is an undeniable challenge for aquatic systems since it is responsible for several environmental and ecological problems and economic losses. Several strategies have been developed to mitigate fouling-related issues in marine environments, including developing marine coatings using nanotechnology and biomimetic models, and incorporating natural compounds, peptides, bacteriophages, or specific enzymes on surfaces. The advantages and limitations of these strategies are discussed in this review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 163 publications
0
7
0
Order By: Relevance
“…The attachment and growth of microorganisms, algae, barnacles, and other aquatic organisms on the surfaces of ships, marine facilities, or other underwater structures in the marine environment is referred to as marine biofouling [1,2]. A globally recognized issue, biofouling leads to surface contamination of vessels and underwater equipment, increased hydrodynamic resistance, corrosion of underwater structures, threats to safe operations, economic losses, and environmental concerns [3]. These challenges significantly impede the development and utilization of marine resources worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The attachment and growth of microorganisms, algae, barnacles, and other aquatic organisms on the surfaces of ships, marine facilities, or other underwater structures in the marine environment is referred to as marine biofouling [1,2]. A globally recognized issue, biofouling leads to surface contamination of vessels and underwater equipment, increased hydrodynamic resistance, corrosion of underwater structures, threats to safe operations, economic losses, and environmental concerns [3]. These challenges significantly impede the development and utilization of marine resources worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Marine biofouling remains a global concern. Numerous approaches have been used to prevent, delay, and control the formation of marine biofilms and the establishment of fouling communities, including the development of antifouling coatings, the use of cleaning technologies and disinfection procedures, and the application of additional methodologies, such as hydrodynamic/acoustic cavitation and thermal stress [ 1 ]. The availability of disinfection treatments to mitigate the effects of marine biofouling is an important requirement for effectively managing marine biosecurity risks, as well as alleviating the consequences of biofouling, including the impact of contamination and/or corrosion, economic costs, and ecological consequences [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since marine biofouling includes the initial formation of biofilms by marine bacteria and diatoms (microfouling), followed by the establishment of larger fouling communities on submerged devices and equipment (macrofouling), a promising approach for biofouling mitigation is to manage macrofouling by delaying microfouling events [ 1 ]. Since cyanobacteria are responsible for starting biofilm formation on submerged surfaces, constitute the major components of marine biofilms [ 25 , 26 , 27 ], and excrete large amounts of EPS [ 28 , 29 ], which are relevant for biofilm cohesion, stability, and structure [ 30 ], these microorganisms may determine the function and arrangement of biofilms [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surface chemical modification is one of the key approaches for endowing marine vessels with antifouling properties. Many materials with universal antifouling functions have been screened out [10][11][12][13][14]. Antifouling surfaces prepared via grafting polymers from initiators or grafting polymers with functional groups have been reported [8,10,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that hydrophilic polymers such as poly(ethylene glycol) and zwitterionic polymers have significant antifouling properties [20][21][22][23]. Copolymers were also regularly reported for antifouling applications [14,24]. Liu et al reported the synthesis of zwitterionic-phosphonic copolymers for the efficient antifouling surface settlement of diverse biomedical metals [25].…”
Section: Introductionmentioning
confidence: 99%